Discovery of velpatasvir (GS-5816): A potent pan-genotypic HCV NS5A inhibitor in the single-tablet regimens Vosevi® and Epclusa®. Issue 16 (15th August 2019) - Link, John O.; Taylor, James G.; Trejo-Martin, Alejandra; Kato, Darryl; Katana, Ashley A.; Krygowski, Evan S.; Yang, Zheng-Yu; Zipfel, Sheila; Cottell, Jeromy J.; Bacon, Elizabeth M.; Tran, Chinh V.; Yang, Cheng Y.; et al.
Graphical abstract: Abstract: Direct-acting antiviral inhibitors have revolutionized the treatment of hepatitis C virus (HCV) infected patients. Herein is described the discovery of velpatasvir (VEL, GS-5816), a potent pan-genotypic HCV NS5A inhibitor that is a component of the only approved pan-genotypic single-tablet regimens (STRs) for the cure of HCV infection. VEL combined with sofosbuvir (SOF) is Epclusa ®, an STR with 98% cure-rates for genotype 1–6 HCV infected patients. Addition of the pan-genotypic HCV NS3/4A protease inhibitor voxilaprevir to SOF/VEL is the STR Vosevi ®, which affords 97% cure-rates for genotype 1–6 HCV patients who have previously failed another treatment regimen.